Access, attendance and performance in urban K8 education during pre- and post-COVID-19 restrictions in Bangladesh: comparison of students in slums, tin-sheds and flats - Alam, Gazi Mahabubul; Mansor, Zawiah; Mahmud, Aidalina; Mohamed Ghazali, Izzuna Mudla (Routledge, 2022)
‘It is dark under the lamp'-a proverb that frequently refers to the misery that prevails in confined, lit environments. In terms of economic development, urban regions have risen to prominence as centers of excellence. Cities are populated by individuals from varied cultural, professional, and economic backgrounds. The disparities in their economic conditions have resulted in several groupings of people who are vastly distinct from their rural counterparts. Comparing urban and rural locations, studies frequently conclude that urban education is significantly superior. This study employs ‘descriptive analysis’ of both secondary and primary data to conclude that students living in urban slums suffer in three K-8 (universal) education characteristics (access, attendance, and academic performance). The government's disregard for students living in slums allowed NGOs to intervene. Students living in shacks are educated mostly through government initiatives in Bangladesh, but those living in apartments attend private, international, and elite-public schools. Students residing in tin huts cannot compete with those residing in apartments, much less slums. This situation has been further compounded by the Covid-19 outbreak. A substantial policy intervention by the Bangladeshi government may be the only possible method to protect the urban K-8 (universal) education of developing nations from criticism.